Drape test of fully formed knitted flared skirts based on 3D-printed human body posture - Cheng Bilian; Jiang Gaoming; Zhang Fanglue; Wan Ailan; Liu Haisang; Li Bingxian; Gao Lizhong (AUTEX Research Journal)
This study proposes a novel drape test method for fully formed knitted flared skirts, specifically tailored to account for the three-dimensional (3D) morphology of the human body. The objective is to accurately assess the drape characteristics of such skirts by developing a comprehensive testing approach. First, a 3D human body model in multiple postures was created using 3ds-Max modeling software and then printed with a 3D printer to serve as a customized test stand. The design and knitting principles for the fully formed flared skirt were examined, and samples were produced using a Shima Seiki four-needle bed computerized flat knitting machine. After fitting the skirt samples onto the 3D-printed human model, drape characteristics were measured with a YG811 drape tester. Using 18 sample skirts, the drape data were analyzed with SPSS26.0 software, revealing that the 3D-printed human model method allows for precise measurement of the drape in fully formed knitted fabrics. This approach offers a more realistic and accurate assessment of drapes, contributing valuable insights for textile design and evaluation in knitted garment production.